Cerebrospinal Fluid Monocyte Chemoattractant Protein‐1 in Alcoholics: Support for a Neuroinflammatory Model of Chronic Alcoholism. (1st April 2014) - Umhau, John C.; Schwandt, Melanie; Solomon, Matthew G.; Yuan, Peixiong; Nugent, Allison; Zarate, Carlos A.; Drevets, Wayne C.; Hall, Samuel D.; George, David T.; Heilig, Markus
<x xml:space="preserve">Abstract</x> Background Liver inflammation in alcoholism has been hypothesized to influence the development of a neuroinflammatory process in the brain characterized by neurodegeneration and altered cognitive function. Monocyte chemoattractant protein‐1/chemokine (C‐C motif) ligand 2 (MCP‐1/CCL2) elevations have been noted in the alcoholic brain at autopsy and may have a role in this process. Methods We studied cerebrospinal fluid (CSF) levels of MCP‐1 as well as interleukin‐1β and tumor necrosis factor‐α in 13 healthy volunteers and 28 alcoholics during weeks 1 and 4 following detoxification. Serum liver enzymes were obtained as markers of alcohol‐related liver inflammation. Results Compared to healthy volunteers, MCP‐1 levels were significantly higher in alcoholics both on day 4 and day 25 (p < 0.0001). Using multiple regression analysis, we found that MCP‐1 concentrations were positively associated with the liver enzymes gamma glutamyltransferase (GGT; p = 0.03) and aspartate aminotransferase/glutamic oxaloacetic transaminase (AST/GOT; p = 0.004). Conclusions These preliminary findings are consistent with the hypothesis that neuroinflammation as indexed by CSF MCP‐1 is associated with alcohol‐induced liver inflammation, as defined by peripheral concentrations of GGT and AST/GOT.